Effects of phenolic monomers on the enzymes activities and volatile fatty acids production of Neocallimastix frontalis B9. - Saad, Wan Zuhainis; Abdullah, Norhani; Alimon, Abdul Razak; Ho, Yin Wan (Elsevier Ltd., 2008)
The effects of phenolic monomers (i.e. ρ-coumaric acid, ferulic acid, ρ-hydroxybenzaldehyde and vanillin) on the enzymes and fermentation activities of Neocallimastix frontalis B9 grown in ball-milled filter paper and guinea grass media were studied. The enzymes studied were carboxymethylcellulase (CMCase), filterpaperase (FPase), xylanase and β-glucosidase. At 96 h of incubation, N. frontalis grown in ball-milled filter paper medium produced comparable xylanase and CMCase activities (0.41, 0.5 μmol/min/mg protein) while in guinea grass medium, N. frontalis produced higher xylanase activity than that of CMCase activity (2.35, 0.05 μmol/min/mg protein). The other enzymes activities were low. When N. frontalis was grown in ball-milled filter paper medium, only acetic acid was produced. However, when grown in guinea grass medium, the major end-product was acetate, but propionic, butyric and isovaleric were also produced in lesser amount. Vanillin showed the least inhibitory effects to enzyme activities of N. frontalis B9 grown in both ball-milled filter paper and guinea grass media. For total volatile fatty acid production, all phenolic monomers showed inhibitory effects, but ρ-coumaric and ferulic acids were the stronger inhibitors than ρ-hydroxybenzaldehyde and vanillin.